Protozoa and Filamentous Bacteria in the First Biological Monitoring Activity of Wastewater Treatment Plants (WWTPs) in La Spezia district (Italy) - Nastro, R.A.; Gambino, E. (Journal of Environmental Accounting and Management, 2026)
Protozoa and filamentous bacteria identification in Mixed Liquor (ML) allowed to obtain detailed information about the performance of five Wastewater Treatment Plants (WWTPs), placed in La Spezia’s District. Microfauna analysis showed the prevalence of testate amoebas (Euglypha spp. prevalent), rotifers and attached ciliate Epistylis plicatis. Low organic load, high sludge-age and high concentration of dissolved oxygen (DO) were well correlated to the growth of Vorticella campanula and Vaginicola sp. Testate amoebas (Euglypha sp. and Arcella sp.) were the most representative group in WWTPs treating also olive mills effluents. Sludge Biotic Index (SBI) showed, for the investigated plants, an optimal to good depuration efficiency (I and II class quality) but it seemed not adequately responsive when olive mills wastewater (rich in phenols) was mixed with the municipal one. Further investigations should be conducted to explain this result. Filamentous bacteria analysis revealed a higher sensitivity of microorganisms to both influent chemical characteristics and WWTPs operational parameters. In most part of the WWTPs, dysfunctions due to the proliferation of filamentous bacteria were detected. In all WWTPs subjected to foaming, the morphotype Nocardia Amarae Like Organisms (NALO), associated with Type 1851 and 0041, was identified as responsible of the foaming. Type 0092 caused a bulking episode in La Spezia WWTP. Haliscomenobacter hydrossis prevailed in the Mixed Liquor (ML) of a plant treating also olive mills wastewater, while Type 0803, 0675 and 1701 were abundant in plants receiving wastewater produced by meat-processing industries. On the whole, filamentous bacteria community analysis represented a more sensitive tool to characterize the activated sludge plant performances in light of providing an adequate management.